Memorandum of Understanding (MoU) and Letter of Agreement between Universiti Teknologi MARA (UiTM) and Universitas Mulawarman - UiTM, Faculty of Business and Management (UiTM, 2023)
On May 15, 2023, Universiti Teknologi MARA (UiTM) and Universitas Mulawarman, Indonesia, solidified their partnership by signing a Memorandum of Understanding (MoU) and Letter of Agreement (LoA). The main objective of this collaboration is to strengthen the bond between the two universities through the exchange of expertise, particularly in teaching, learning, and research initiatives. The Vice Chancellor of UiTM, Professor Datuk Ts. Dr. Hajah Roziah Mohd Janor, entrusted Professor Dr. Firdaus Abdullah, the Dean of the Faculty of Business and Management (FBM), to sign the MoU and LoA. The signing ceremony was attended by Associate Prof. Dr. Zarina Denan, Deputy Dean (Academic) of Faculty Business and Management, Dr. Ir. H. Abdunnur, Rector of Universitas Mulawarman, and Prof. Dr. Syarifah Hudayah, Dean of Fakultas Ekonomi and Bisnis of Universitas Mulawarman.